New Light on John Davy. (3rd July 2019) - Lacey, Andrew
Abstract : John Davy (1790–1868), the only brother of Sir Humphry Davy (1778–1829), was an army doctor, serving overseas, in various posts, in Belgium, France, Ceylon, the Ionian Islands, Malta, and the West Indies. He was also a researcher, a writer in his own right, and the editor of his brother's works. This study, drawing principally on three unpublished manuscript sources recovered during work on the Davy Letters Project, examines a crucial, formative period in John Davy's life – the years 1808–1814 – and situates him in the cultures and networks, scientific and literary, of which he was part. It explores John Davy's time working as an assistant at the Royal Institution (1808–1811), a period he spent in Edinburgh as a student (1811–1813), and his engagement there in a scientific dispute with John Murray (1778–1820) over the chemical composition of muriatic acid gas, and the time he spent in his native Cornwall in 1814, prior to his first medical posting with the military.